Peran Pesantren Entrepreneur Dalam Pengembangan Masyarakat - Zainal Arif; Efri Syamsul Bahri; Zulfitria Zulfitria; Muhammad Shibgotullah (Al Maal: Journal of Islamic Economics and Banking, 2020)
Pesantren Entrepreneur is an Islamic dormitory school which has dakwah activity as well as a business activity. Business activity becomes one of society development indicator. In a hadith, Rasul Saw said, 9 of 10 luck is from trading. Unfortunately, it is many people still think to get a luck by becoming an employer. Run a business is a way to get a luck that people can do. Moreover, Indonesia is a country which has so much of natural resources. But up to now, many Indonesian are unable to take that great chance. Indonesia has a great potential. If Indonesian are able to take the chance then the poverty will easily to be removed. And in Pesantren Entrepreneur has many programs of society empowerment, particularly in a small micro enterprise sector. Based on the statement above, it is so interesting to discuss about Society Empowerment and the steps in Pesantren Entrepreneur to Empower Society in Small Micro Enterprise sector